2015
DOI: 10.3109/10428194.2015.1026900
|View full text |Cite
|
Sign up to set email alerts
|

NPM1 mutations may reveal acute myeloid leukemia in cases otherwise morphologically diagnosed as myelodysplastic syndromes or myelodysplastic/myeloproliferative neoplasms

Abstract: NPM1 mutations may reveal acute myeloid leukemia in cases otherwise morphologically diagnosed as myelodysplastic syndromes or myelodysplastic/myeloproliferative neoplasms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…As expected for founder genetic lesions, NPM1 mutations are specific, being almost exclusively restricted to AML, usually de novo, and generally expressed in the whole leukemic population [ 13 , 14 , 20 ]. Notably, NPM1 -mutated AML, showing distinctive genetic, pathologic, immunophenotypic and clinical features, has now been recognized as a full distinct entity among AML with recurrent genetic abnormalities in the 2016 revision of World Health Organization (WHO) classification of myeloid neoplasms and acute leukemia [ 21 ].…”
Section: Npm1 Mutations In Aml: Biological and mentioning
confidence: 99%
See 1 more Smart Citation
“…As expected for founder genetic lesions, NPM1 mutations are specific, being almost exclusively restricted to AML, usually de novo, and generally expressed in the whole leukemic population [ 13 , 14 , 20 ]. Notably, NPM1 -mutated AML, showing distinctive genetic, pathologic, immunophenotypic and clinical features, has now been recognized as a full distinct entity among AML with recurrent genetic abnormalities in the 2016 revision of World Health Organization (WHO) classification of myeloid neoplasms and acute leukemia [ 21 ].…”
Section: Npm1 Mutations In Aml: Biological and mentioning
confidence: 99%
“…High NPM1 -mutated allele burden at diagnosis was an independent predictor of unfavorable clinical outcomes, particularly in patients who received HSCT in first CR and in the subgroup of subjects with concomitant DNMT3A mutations. Because of BM multilineage involvement of NPM1 mutations not being restricted to cells with blast morphology [ 12 , 16 , 20 ], the VAF could in fact reveal the true clonal disease burden. Higher NPM1 mutant allele burden may be less amenable to eradication by intensive chemotherapy, potentially resulting in a higher likelihood of MRD persistence.…”
Section: Npm1 Mutation Levels At Aml Diagnosismentioning
confidence: 99%
“…Nucleophosmin ( NPM1 ) gene mutations, occurring in approximately 30% of adult acute myeloid leukemia (AML) cases, and in 50–60% of AML cases with a normal karyotype, represent one of the most frequent molecular lesions observed in AML [13]. Moreover, NPM1 mutations are specific, being almost exclusively restricted to AML, and usually expressed in the entire leukemic population [1, 4, 5]. As expected for founder genetic lesions, they are also stable throughout the course of the disease, with NPM1 mutations almost invariably documented in patients experiencing AML relapse [4] Most importantly, NPM1 mutations result in structural changes of the C-terminus of the NPM1 protein, with subsequent aberrant cytoplasmic delocalization, leading to perturbations in multiple cellular pathways, critical for leukemogenesis [1, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been reported that the sequential induction of DNMT3A and nucleophosmin (NPM1) mutations in genetically engineered mice can generate an MPN-like disorder, following a condition of clonal hematopoiesis [23]. Nonetheless, NPM1 mutations are not found in MPNs in humans and are only exceptionally detected in non-acute myeloid neoplasms sharing dysplastic features (either purely myelodysplastic or myelodysplastic/myeloproliferative), multilineage involvement and excess of blasts, causing controversies about the pathological classification of these uncommon cases [24][25][26].…”
Section: Introductionmentioning
confidence: 99%